DIGIMO: MODULAR IOT-BASED BIOGAS AND BIO-SLURRY SYSTEM FOR LIVESTOCK ENERGY TRANSITION - Giza Unika Anantasa (Jurnal Geosaintek, 2026)
The transformation of livestock waste into renewable energy presents a promising pathway to support Indonesia's low carbon energy transition, especially in rural communities. This paper introduces DIGIMO (Digester Modular IoT and Bio- Slurry), an innovative biogas system designed for small scale farming villages. DIGIMO integrates three key innovations: a modular digester design that allows scalable and flexible installation based on the number of livestock, a low cost IoT based monitoring system using sensors to track temperature, gas pressure, and gas volume for optimal fermentation, and a bio-slurry refinement unit that converts biogas residue into high-nutrient organic liquid fertilizer. The biogas produced is primarily distributed directly to local households for cooking and daily energy use, reducing their reliance on fossil-based fuels. Meanwhile, the processed slurry provides additional economic value as a sustainable agricultural input. This model not only reduces greenhouse gas emissions but also promotes circular economy principles by closing the loop between energy and agriculture. The proposed DIGIMO system aims to be replicable across Indonesia’s rural areas, combining environmental benefits, energy security, and rural economic empowerment. This paper highlights the design, process flow, and potential impacts of DIGIMO as a feasible low carbon energy business innovation for Indonesia’s sustainable energy future.